A new cryptostome bryozoan Ptilotrypa from the Upper Ordovician Yong Limestone Formation: Tethyan sequence of Kumaun Higher Himalaya, India. (12th February 2019) - Swami, Narendra K.; Ernst, Andrej; Tripathi, Satish C.; Barman, Prasenjit; Bharti, S.K.; Rana, Y.P.
Abstract: A new species of the Paleozoic bryozoan genus Ptilotrypa of the order Cryptostomata is described from the lower part of the Yong Limestone Formation, Katian, Upper Ordovician of the Kumaun Tethys Himalaya: Ptilotrypa bajpaii new species. The presence of the genus Ptilotrypa in the Tethyan Himalaya suggests paleogeographic connections to the Upper Ordovician of North America and, consequently, Upper Ordovician age for the lower part of the Yong Limestone Formation. This species displays a reticulate colony shape, which suggests an efficient filtering capacity in an environment with a high primary production. Morphological peculiarities and systematic assignment of the genus Ptilotrypa are discussed. UUID: http://zoobank.org/898276c8-2924-4da2-ae96-3392cb2ebbc3